Non-lethal foam deployment system for vehicle stopping - Schroeder, Matthew E. (Kansas State University, 2010)
The military is interested in stopping suspicious vehicles at checkpoints or security positions while minimizing noncombatant fatalities. Preliminary work has shown that decreasing the oxygen concentration in proximity to the automobile air intake system and blocking the air flow through an automotive induction system provides the greatest probability of success for the broadest possible array of internal combustion engines. A non-lethal foam deployment system was developed that satisfies the military’s needs to stop suspicious vehicles. The foam is discharged from a pressurized tank and engulfs the air intake system of the target vehicle. The foam is drawn into the air intake and the protein additive contained in the foam would occlude pores in the air filter medium. Once the air filter was blocked, the vehicle would become immobilized so that security personnel can secure the vehicle. The work carried out in this project consisted of development and refinement of surfactant solution composition, improvement in the rate of absorption of carbon dioxide for increased foam volume, and characterization of discharge for optimum foam volume. In addition, a half-scale model apparatus was developed to test the foam’s ability to be ingested in an automotive intake system. These experiments demonstrated that the foam deployment system would stop an automobile within six seconds.
Keywords: Non-Lethal; Vehicle Stopping; Foam; Engineering, Chemical (0542)